2006
DOI: 10.1186/1471-2474-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound tissue characterization in shoulder and thigh muscles – a new approach

Abstract: BackgroundThe echogenicity patterns of ultrasound scans contain information of tissue composition in muscles. The aim was: (1) to develop a quantitative ultrasound image analysis to characterize tissue composition in terms of intensity and structure of the ultrasound images, and (2) to use the method for characterization of ultrasound images of the supraspinatus muscle, and the vastus lateralis muscle.MethodsComputerized texture analyses employing first-order and higher-order grey-scale statistics were develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 24 publications
(27 reference statements)
2
75
0
3
Order By: Relevance
“…The RF muscle which forms part of a major muscle in the body, the quadriceps, is a long bipennate muscle with two rows of muscle fibres to allow greater power but less range of motion, while BB is a small spindle shaped muscle with short tendinous structure. Nielsen et al (2006) reported that the vastus lateralis muscle, another component of the quadriceps, contained more non-contractile components than supraspinatus muscle in the upper limb, using ultrasound imaging. It is possible that the overall greater tone and stiffness in the RF muscle observed in the present study could be as a result of the differences in non-contractile components in the lower limb muscle compared to those in the BB muscle.…”
Section: Differences In Mechanical Parameters Between Musclesmentioning
confidence: 99%
“…The RF muscle which forms part of a major muscle in the body, the quadriceps, is a long bipennate muscle with two rows of muscle fibres to allow greater power but less range of motion, while BB is a small spindle shaped muscle with short tendinous structure. Nielsen et al (2006) reported that the vastus lateralis muscle, another component of the quadriceps, contained more non-contractile components than supraspinatus muscle in the upper limb, using ultrasound imaging. It is possible that the overall greater tone and stiffness in the RF muscle observed in the present study could be as a result of the differences in non-contractile components in the lower limb muscle compared to those in the BB muscle.…”
Section: Differences In Mechanical Parameters Between Musclesmentioning
confidence: 99%
“…Pisels were given a value ranging from 0, pure black, to 255, pure white 15) . Dorsiflexion was measured with a goniometer (steal Goniometer stainless, BaseLine, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is easy to use and non-invasive; it is possible to compare both sides, there no risk of exposure to radioaction compared to magnetic resonance imaging (MRI) or computerized tomography (CT), and it is cheap 14) . Nielsen et al 15) reported that evaluation of muscle density and the white area index can be used for analyzing qualitative structure, and Sipila et al 16) reported measuring the cross of the tibialis anterior with ultrasonography and calculating its volume.…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al, (2006), para la caracterización y descripción de la musculatura mediante imagen ecográfica. Aunque estos autores sólo utilizaron parámetros de primer orden y no las matrices de concurrencia.…”
Section: Introductionunclassified